ANALISIS BEBERAPA FAKTOR YANG BERPENGARUH TERHADAP PENDAPATAN KEPALA RUMAH TANGGA MISKIN DI KECAMATAN SERIRIT KABUPATEN BULELENG - Winda Yani, Ni Putu; Indrajaya, I Gusti Bagus (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 7, No. 3, Maret 2018 (pp. 381-619), 2018)
This research was conducted on poor households in District Seririt Buleleng District. The purpose of this study is to analyze the influence of education level, type of work and the number of dependents have a significant effect simultaneously on the income of poor household heads in District Seririt Buleleng District. Analyzing the influence of education level, type of work and the number of dependents significantly partially affect the income of poor household heads in District Seririt Buleleng District. Analyzing the dominant influence among education level, type of work and the number of dependents on income of poor household head in District Seririt Buleleng Regency. The results of this study are the level of education, type of work, and the number of dependents simultaneously significant effect on the income of poor heads of households. The level of education, the type of work, and the number of dependents partially have a positive and significant impact on the income of poor household heads. The most dominant independent variables affecting the income of poor household heads in Seririt District are the dependent variable variables. Keywords : income, poor households, poverty, education, employment